Qualitative and Quantitative Analtsis of Teak Saw Logs of Bastar Forests - Suri, S. K. (Indian Forester, 1974)
Based on the auction results of six major depots of Bastar Circle for the forest year 1970-71 and 1971-72, percentage volume distribution of teak saw logs by grades and sizes has been analysed. Volumes of Teak saw logs of grades I, II and III constitute 16%, 48% and 18% respectively. Cumulafive curves for long sizes for grades I, II and III have also been constructed and method detailed.